(untitled) (Journal of human and social sciences, 2025)
Surah Yusuf (peace be upon him) is one of the blessed chapters revealed by Allah Almighty to His Messenger (peace and blessings be upon him). It contains the complete story of Prophet Yusuf, and it is described by Allah at the beginning of the chapter as “the best of stories.” Upon reflecting deeply on this Surah, a range of elevated humanitarian values becomes evident. These include commendable traits such as patience, honesty, chastity, and generosity, as well as blameworthy traits such as lying, envy, and deceit. This Surah truly represents a moral school that teaches believers how to face hardships with patience and steadfastness, while staying connected to noble values in all circumstances.